e-conomics Supplements: The Antidote to Teaching and Learning Economics through Open and Distance Learning - Kek , Lilian Siew Yick; Chiam , Chooi Chea (2009)
Teaching and learning through distance education can be challenging for both the educator and the learner. The challenges are further intensified for quantitative courses such as Mathematics, Accounting, Finance and Economics. In conventional settings, learning occurs during classroom activities whereby learners do hands-on exercises, trial-and-error practices, and obtain on-the-spot feedback from their teachers throughout the course. Distant learners, on the other hand, mainly struggle through these courses in isolation. Educators also find it difficult to develop teaching and learning activities that cater to the needs of these isolated learners. Besides encouraging independent learning, they must also keep learners engaged, motivated and focused throughout the course. Due to the difficulty level of the courses, it is not surprising that these learners usually perform below average in their assessments. At the Open University Malaysia (OUM), The Economics Support Team (TEST) was formed to address the above issue. The team, made up of 5 subject matter experts in the field of Economics, designed a unique teaching and learning supplement, áº½-conomics to support a level-4 course, Principles of Macroeconomics. A total of 60 learners from two OUM learning centres who participated in the study, received the áº½-conomics supplements periodically throughout the course. At the end of the course, data was gathered from the participants using a 20-items questionnaire. The performances of the participants were then compared to the overall learner performance for the course. Results were tabulated and analysed using descriptive statistics. This study aims to determine the effectiveness of áº½-conomics supplements in (1) enhancing teaching and learning activities (2) instill interest, motivation and confidence to learn the course; and (3) improve overall performance of learners in the course. The outcome of this study will be useful for Open and Distance Learning institutions to produce effective teaching and learning activities for Economics and other quantitative courses delivered through open distance learning. (Authors' abstract)